Peuple de l'ombre, peuple universel : les résistants et les anciens résistants français face à l'Empire et la décolonisation (1940-1962) - Houle, Vincent (Université de Montréal, 2022)
This thesis examines French resistants and ex-resistants’ ties with the Empire, during and after the Second World War. It therefore explores a broader timeframe and geographic area than what previous historiography about French Resistance has offered up until now. In analyzing French Resistance newspapers and constitutional projects from 1940 through 1944, the thesis reveals that while the principles of the Third Republic were repudiated by French society at the time, one particular element remained: the idea of the civilizing mission. Then, through the study of numerous personal testimonies covering the years between the Liberation and the end of the Algerian War, the research offers a profound and nuanced insight on ex-resistants views of the Empire and their point of view on their country's colonial system. After 1944, the power dynamic shifted to the resistants: they were no longer dominated by a violent German state, they were now the ones enforcing domination to the colonies. The testimonies reveal the internal conflict French ex-resistants were dealing with when faced with the problems of decolonization. It also shows how the principles, for which they risked their lives during the war, were modified or reshaped to fit with their views on how to deal with the colonies’ wishes for emancipation. In examining how the war against fascism and the Vichy regime impacted personal attitudes towards the Empire and the exercise of domination, the study offers a new perspective on the French Resistance and French Imperial history from 1940 to 1962, one that accounts for political and economic imperatives as well as for the importance of the different interpretations of the Republic's core principles for these individuals. The individuals were selected because of the importance of their political, social or military commitments through the period. By focusing on the relationships between these successive commitments, the analysis enlarges the scope through which the French Resistance must be understood.
Keywords: Algeria; Algérie; Decolonization; Deuxième Guerre mondiale; Décolonisation; Empire français; European history / Histoire de l’Europe (UMI : 0335); France; French Empire; French Resistance; Imperialism; Impérialisme; Indochina; Indochine; Republicanism; Républicanisme; Résistance française; Second World War; Universalism; Universalisme